2019
DOI: 10.1021/acs.biomac.9b01282
|View full text |Cite
|
Sign up to set email alerts
|

Replacing Cu(II)Br2 with Me6-TREN in Biphasic Cu(0)/TREN Catalyzed SET-LRP Reveals the Mixed-Ligand Effect

Abstract: The mixed-ligand system consisting of tris(2-aminoethyl)amine (TREN) and tris(2-dimethylaminoethyl)amine (Me 6 -TREN) during the Cu(0) wire-catalyzed single electron transfer-living radical polymerization (SET-LRP) of methyl acrylate (MA) in "programmed" biphasic mixtures of the dipolar aprotic solvents NMP, DMF, and DMAc with H 2 O is reported. Kinetic and chain end analysis studies by NMR and MALDI-TOF before and after thio-bromo "click" reaction demonstrated that Me 6 -TREN complements and makes the less ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 88 publications
0
20
0
Order By: Relevance
“…The polymerization reactions were allowed to run in either open or closed vials. It is important to note that in our system, activation, disproportionation and deactivation steps take place in different compartments via partitioning of the ligand and copper active species, as has been recently postulated for "programmed" biphasic SET-LRP systems [37][38][39] . In this sense, the activation step proceeds in the organic phase (oil phase) via outer sphere single electron transfer process (OSET), where Cu(0) acts as an electron donor to promote the heterolytic cleavage of the alkyl halide bond to generate the active radicals 40 .…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The polymerization reactions were allowed to run in either open or closed vials. It is important to note that in our system, activation, disproportionation and deactivation steps take place in different compartments via partitioning of the ligand and copper active species, as has been recently postulated for "programmed" biphasic SET-LRP systems [37][38][39] . In this sense, the activation step proceeds in the organic phase (oil phase) via outer sphere single electron transfer process (OSET), where Cu(0) acts as an electron donor to promote the heterolytic cleavage of the alkyl halide bond to generate the active radicals 40 .…”
Section: Resultsmentioning
confidence: 84%
“…Afterwards, the generated Cu(I)-ligand complex formed during the activation step migrate to the aqueous phase where the crucial disproportionation step takes place, giving rise to the Cu(II)-ligand complex and in situ nascent Cu(0). In this context, the deactivation step is postulated to take place in the interphase between the aqueous and oil phases, via a reverse OSET process mediated by Cu(II)-ligand complex 37 . Therefore, the surface area of the polymeric microdroplets and an efficient partition of the ligand between aqueous and organic (oil) phases are crucial aspects in our system to provide an efficient deactivation step and therefore provide control over the polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…This would reduce the number of CTAs required to just two, while still allowing access to a wide range of dispersity values. In Cu(0)-mediated RDRP, mixed ligand systems have recently been realized, albeit not to control the dispersity 48,49 but to the best of our knowledge, the concept of mixing RAFT agents prior to polymerization has not been implemented before and can be summarized in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the Cu I species can also form Cu(0) nanoparticles and the Cu II species via disproportionation, i.e., there is a disproportionation/comproportionation equilibrium between the copper plate and the substrate, especially in aqueous media. 37,38 The copper species (Cu I , Cu(0) nanoparticles, and Cu II ) play important roles in regulating the polymer brush growth in SI-CuCRP. It has been reported that the solvent composition, external CuBr 2 , the nature of the monomer and ligand concentration dramatically affect the disproportionation/comproportionation equilibrium and the aqueous polymerization.…”
Section: Introductionmentioning
confidence: 99%